Molecular Detection of Some Virulence Genes in E. coli Isolated from Urinary Tract Infections - Al-Wakeel, Mays Ibrahim; Alnasrawi, Abeer M.; Al-Mamoori, Zahraa Z.; Al-Ghanimi, Ali Abdul Kadhim (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Urinary tract infections (UTIs) are among the most prevalent bacterial infections worldwide, predominantly affecting women and often caused by Escherichia coli (E. coli). Specific Background: The pathogenicity of E. coli in UTIs is primarily associated with its virulence genes, which enable bacterial adhesion, toxin production, and iron acquisition, thus facilitating colonization and persistence in the urinary tract. Knowledge Gap: Despite extensive research, the prevalence and distribution of major virulence genes among E. coli isolates in specific regions, such as Karbala, Iraq, remain insufficiently characterized. Aims: This study aimed to detect five virulence genes (HlyA, papC, iutA, CNF-1, and Sfas) in E. coli isolates obtained from women with UTIs, using molecular PCR techniques. Results: Among 24 isolates, the genes HlyA, papC, CNF-1, and Sfas were detected in 45.83%, 50%, 37.5%, and 37.5% of samples respectively, while iutA was absent. Novelty: This is one of the few studies providing molecular evidence of virulence gene distribution in UTI-associated E. coli within Iraq, highlighting regional variation compared to previous international reports. Implications: The findings enhance understanding of the molecular basis of UTI pathogenicity and may inform the development of targeted diagnostic and therapeutic strategies.Highlight : The study identifies the distribution of five major virulence genes in E. coli isolated from UTI cases. PCR analysis reveals variation in gene frequency, indicating differing pathogenic potentials among isolates. The findings emphasize the importance of gene detection for improving therapeutic and preventive strategies against E. coli infections. Keywords : CNF-1, HlyA, iutA, papC, Sfas, UTI